This is our music : free jazz, the Sixties, and American culture - Anderson, Iain, 1967- (Arts and intellectual life in modern America., 2007)
By examining the production, presentation, and reception of experimental music by Ornette Coleman, Cecil Taylor, John Coltrane, and others, Iain Anderson traces the strange, unexpected, and at times deeply ironic intersections between free jazz, avant-garde artistic movements, Sixties politics, and patronage networks. Anderson emphasizes free improvisation's enormous impact on jazz music's institutional standing, despite ongoing resistance from some of its biggest beneficiaries. He concludes that attempts by African American artists and intellectuals to define a place for themselves in American life, structural changes in the music industry, and the rise of nonprofit sponsorship portended a significant transformation of established cultural standards. At the same time, free improvisation's growing prestige depended in part upon traditional highbrow criteria: increasingly esoteric styles, changing venues and audience behavior, European sanction, withdrawal from the marketplace, and the professionalization of criticism. Thus jazz music's performers and supporters - and potentially those in other arts - have both challenged and accommodated themselves to an ongoing process of cultural stratification.